Konferencja naukowa doktorantów i studentów Instytutu Historii i Stosunków Międzynarodowych UPH - SIEBIESZUK, Damian (Historia i Świat, 2015)
Overview and description of the Regional Scientific Conference "From Our Research - PhD students and students of the Institute of History and International Relations" at Siedlce University (2014.11.24)